2020
DOI: 10.1111/anu.13163
|View full text |Cite
|
Sign up to set email alerts
|

Dietary choline improves growth performance, antioxidant ability and reduces lipid metabolites in practical diet for juvenile Pacific white shrimp, Litopenaeus vannamei

Abstract: An 8‐week feeding trial was conducted to evaluate the effects of dietary choline levels on growth performance, antioxidant capacity and lipid metabolites in juvenile Pacific white shrimp. Six isonitrogenous and isolipidic diets were formulated to supply 0, 1,000, 2,000, 4,000, 6,000, 10,000 mg/kg choline chloride, and dietary choline levels were analysed to be 1,317 (basal diet), 1,721, 2,336, 3,294, 5,421 and 9,495 mg/kg, respectively. Dietary choline levels significantly influenced percent weight gain (PWG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…Therefore, choline might reduce phosphatidylcholine content in L. vannamei, resulting in a decrease in hemolymph lipid content. Moreover, dietary choline had no statistical effect on hemolymph cholesterol and triglyceride contents of L. vannamei [21]. In this study, no significant difference was found in serum triglyceride among all treatment groups, while the serum total cholesterol in shrimp fed 6000 mg/kg choline was significantly higher than that in shrimp fed 4000 mg/kg choline.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Therefore, choline might reduce phosphatidylcholine content in L. vannamei, resulting in a decrease in hemolymph lipid content. Moreover, dietary choline had no statistical effect on hemolymph cholesterol and triglyceride contents of L. vannamei [21]. In this study, no significant difference was found in serum triglyceride among all treatment groups, while the serum total cholesterol in shrimp fed 6000 mg/kg choline was significantly higher than that in shrimp fed 4000 mg/kg choline.…”
Section: Discussioncontrasting
confidence: 67%
“…Similarly, P. monodon fed choline-deficient diets have higher hepatopancreatic lipid concentration than that of shrimp fed with supplemented choline chloride [9]. On the contrary, higher concentrations of lipid metabolites in hemolymph, including high-density lipoprotein and low-density lipoprotein, were found in L. vannamei fed the basal diet [21]. In this study, compared with shrimp fed 0 mg/kg choline, phosphatidylcholine (lecithin) was downregulated in shrimp fed 6000 mg/kg choline (Supplementary Figure S1B).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Decreased levels and activity of antioxidants like SOD and CAT have also been linked to Alzheimer’s disease, according to several studies [ 100 , 101 ]. In addition, Nabila [ 102 ] and Shi [ 103 ] reported choline’s antioxidant capacity, strengthening the positive effect of the co-treatment of jambolan extract and choline.…”
Section: Discussionmentioning
confidence: 99%